Pedagogical Competency, Teacher Work Groups, and Motivation: Their Influence on Teaching Performance in State Elementary Schools - Abdullah; Musdiani; Putra, Mulia; Sari, Siti Mayang (Universitas Veteran Bangun Nusantara, 2024)
The quality of teaching is crucial for effective education and student achievement. This research investigates the impact of pedagogical competency training, teacher work groups, and work motivation on the teaching performance of elementary school teachers. Employing a quantitative approach, the study uses correlation research methods to analyze data collected through questionnaires and documentation. The analysis, conducted with SPSS, includes validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. The findings reveal that while pedagogical competency training does not have a significant partial effect on teaching performance, work motivation significantly influences it. Moreover, the combined effect of pedagogical competency training, teacher work groups, and work motivation demonstrates a significant impact on teaching performance. This study contributes to the education field by highlighting the importance of teacher motivation and the synergistic effects of various professional development strategies on teaching performance.